Economic Barriers to Educational Access: A Literature Review - Burhan, Imron; Musfirah; Nur Fadny Yuliani; Siswati Rachman; Amriadi (Cita konsultindo, 2025)
Economic barriers are one of the primary factors affecting access to and the quality of education in Indonesia. Income inequality leads to disparities in educational opportunities, with students from lower-income families facing significant limitations in accessing adequate educational services. This study aims to examine the relationship between economic factors and educational access in Indonesia through a literature review approach. The findings reveal that financial constraints impact school affordability, availability of learning facilities, and students’ motivation to pursue higher levels of education. Although the government allocates 20% of the national budget to education, its distribution and utilization remain uneven. Therefore, more inclusive policies are needed, such as expanding scholarship programs, reducing education costs, and improving educational infrastructure in underdeveloped regions. Collaboration among the government, communities, and the private sector is essential to ensure equitable and high-quality access to education. These efforts are expected to contribute to the development of a more competitive and globally capable human resource base.